CD335 (NKp46)+ T-Cell Recruitment to the Bovine Upper Respiratory Tract during a Primary Bovine Herpesvirus-1 Infection - Osman, Rahwa A.; Griebel, Philip John (Frontiers in Immunology, 2017)
Bovine Natural Killer (NK) cells were originally defined by the NK activation receptor CD335 (NKp46) but following the discovery of NKp46 expression on human T-cells the definition of conventional bovine NK cells was modified to CD335+CD3- cells. Recently, a bovine T cell population co-expressing CD335 was identified and these non-conventional T-cells were shown to produce IFN- and share functional properties with both conventional NK cells and T-cells. It is not known, however, if CD335+ bovine T cells are recruited to mucosal surfaces and what chemokines play a role in recruiting this unique T cell subpopulation. In this study, bovine herpesvirus -1 (BHV-1), which is closely related to herpes simplex virus-1, was used to investigate bovine lymphocyte cell populations recruited to the upper respiratory tract (URT) following a primary respiratory infection. Immunohistochemical staining with individual monoclonal antibodies revealed significant (P < 0.05) recruitment of CD335+, CD3+ and CD8+ lymphocyte populations to the nasal turbinates on day 5 following primary BHV-1 infection. Dual-colour immunofluorescence revealed that cells recruited to nasal turbinates were primarily T cells that co-expressed both CD335 and CD8. This non-conventional T cell population represented 77.5% of CD355+ cells and 89.5% of CD8+ cells recruited to nasal turbinates on day 5 post-BHV-1 infection. However, due to diffuse IFN- staining of nasal turbinate tissue, it was not possible to directly link increased IFN- production following BHV-1 infection with the recruitment of non-conventional T-cells. Transcriptional analysis revealed CCL4, CCL5 and CXCL9 gene expression was significantly (P < 0.05) up-regulated in nasal turbinate tissue following BHV-1 infection. Therefore, no single chemokine was associated with recruitment of non-conventional T-cells. In conclusion, the specific recruitment of CD335+ and CD8+ non-conventional T cells to viral infected tissue suggests these cells may play an important role in either the clearance of a primary BHV-1 infection or regulating host responses during viral infection. The early recruitment of non-conventional T-cells following a primary viral infection may enable the host to recognize viral infected cells through NKp46 while retaining the possibility of establishing T cell immune memory.